The “great reason of the body". Some remarks on Nietzsche's influence on neopragmatism and somaesthetics - Marino, Stefano (Scenari, 2023)
In this article I offer a reconstruction and interpretation of the reception of Friedrich W. Nietzsche’s thinking in the context of contemporary neopragmatism. In particular, in my reconstruction and interpretation I focus on two leading figures of contemporary neopragmatist philosophy, Richard Rorty and Richard Shusterman. As is well-known, the latter has eventually developed neopragmatism in a particular aesthetic direction in the last twenty years, namely in the direction of a new disciplinary proposal called somaesthetics. The first section of my article deals, in general, with the great role played by the reception of Nietzsche’s thinking in 20th-century philosophy and culture. The second section of my article is specifically dedicated to Rorty’s unique neopragmatist interpretation of Nietzsche, characterized by a particular focus on the role of a linguistically mediated interpretive access to the real. The third and final section of my article shifts my attention from Rorty to Shusterman, first offering a brief explanation of some differences between Rorty’s and Shusterman’s versions of neopragmatism, and then focusing my attention on Shusterman’s particular interpretation of Nietzsche: an interpretation that, in comparison to Rorty’s, is mostly centred on the role of the body in the human experience of the world, rather than on the supposedly “absolute” and exclusive role of language and interpretation.